Using Principal Component Scores and Artificial Neural Networks in Predicting Water Quality Index - Khan, Rashid Atta; Zain, Sharifuddin M.; Juahir, Hafizan; Yusoff, Mohd Kamil; T.I., Tg Hanidza (IntechOpen, 2012)
None